Exploring Social Remittances and Transnational Activism Amongst Transgender Refugees - Soloaga, Isabel (Frontiers in Human Dynamics, 2021)
This paper explores the concept of social remittances in a new way by mapping it onto existing empirical research with transgender refugees living in the UK and the United States. Utilising social remittances and transnational ties to leverage their activism across borders, transgender refugees in both origin and receiving countries engage in activism in order to petition for access to basic rights within intolerant social and political spheres. Focusing on three case studies, it analyses the role of social remittances and transnational ties in the activism of transgender refugees both in origin and receiving countries. Social remittances influence the migrations and aspirations of transgender individuals in origin countries by diffusing knowledge about different gender and sexual identities, as well as potential legal protections abroad. Encountering deeply transphobic surroundings in both their origin countries and within the receiving countries to which they flee, transgender refugees rely on social remittances to inform themselves and turn to activism in order to survive. Moreover, systemic oppression, racism and transphobia in receiving countries necessitates the maintenance of these transnational channels and pushes transgender refugees, victims of systemic violence worldwide, into roles as activists. In conclusion, transgender refugees provide one important example of a group that relies strongly on transnational activism in order to survive, not only in their home countries but also in the allegedly “safe countries” to which they flee.